3(y-5)/4-4y=3(y-3)/2

Simple and best practice solution for 3(y-5)/4-4y=3(y-3)/2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y-5)/4-4y=3(y-3)/2 equation:


y in (-oo:+oo)

(3*(y-5))/4-(4*y) = (3*(y-3))/2 // - (3*(y-3))/2

(3*(y-5))/4-((3*(y-3))/2)-(4*y) = 0

(3*(y-5))/4+(-3/2)*(y-3)-4*y = 0

(3*(y-5))/4-3/2*(y-3)-4*y = 0

(3*(y-5))/4+(-3/2*4*(y-3))/4+(-4*4*y)/4 = 0

3*(y-5)-3/2*4*(y-3)-4*4*y = 0

3-3*y-16*y = 0

3-19*y = 0

(3-19*y)/4 = 0

(3-19*y)/4 = 0 // * 4

3-19*y = 0

3-19*y = 0 // - 3

-19*y = -3 // : -19

y = -3/(-19)

y = 3/19

y = 3/19

See similar equations:

| -x+14=-5x+6 | | -7x+16=-3x-16 | | 11x-5=4x+37 | | 4x+19=-2x+61 | | -24=8-(8*r) | | -4x+19=47 | | -4x+11=19 | | -24=8-8r | | 9x+11=2x+74 | | 3a+4b-a-2b= | | f(2)-f(5)=8x-12 | | 4y-x+8=0findy | | 11(2b-1)-(3b-7)=1 | | 5(x-2)=7x-16 | | dy/y^2=x | | (8x-9)(x-7)= | | ln(4y)=x | | -1/4(12-8x)-2x=3 | | 4senx+3cosx=3 | | -2x=-3y-5 | | xy+5y=3 | | -7x+17=-3x+1 | | x+11=-3x-9 | | 2(5x-3)=4x-18 | | -26=4(3x-3)-2 | | 2(x+1)+5=5x+19 | | -4x+34=4(2x-3)-2 | | 9x-5=6x-26 | | 22x(3x+4)=484 | | (2x^2)+34x+144=0 | | 4N+13=57 | | 8y-12=30 |

Equations solver categories